A Study on the Influence of FDM Parameters on the Compressive Behavior of PET-G Parts - Zisopol, Dragos Gabriel; Minescu, Mihail; Iacob, Dragos Valentin (Engineering, Technology & Applied Science Research, 2024)
This article presents the results of a study on the influence of Fused Deposition Modeling (FDM) 3D printing parameters on the compressive behavior of test specimens made of PET-G. In this context, 45 test specimens, made by FDM on the Anycubic 4 Max Pro 2.0 printer, were compressive tested on a universal testing machine Barrus White 20 kN, with the height of the layer applied in one pass being Lh = 0.10/0.15/0.20 mm and filling percentage Id = 50/75/100%. The two considered variable parameters, Lh and Id influence the compression resistance of the PET-G parts, with Id having a more significant influence. The scope and novelty of this work is to find the optimal parameters for maximum compressive strength (Cs) of PET-G samples made of FDM.